2015
DOI: 10.5194/sed-7-3511-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil erosion assessment and control in Northeast Wollega, Ethiopia

Abstract: Abstract. Soil erosion is the main driver of land degradation in Ethiopia, and in the whole region of East Africa. This study was conducted at the Northeast Wollega in West Ethiopia to estimate the soil losses by means of the Revised Universal Soil Loss Equation (RUSLE). The purpose of this paper is to identify erosion spot areas and target locations for appropriate development of soil and water conservation measures. Fieldwork and household survey were conducted to identify major determinants of soil erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…DOI: http://doi.org/10.17352/2455-815X.000038 Therefore, information on land use/land cover changes, its ultimate impact and possibilities for their optimal use is essential for the selection, planning and implementation of land use schemes to meet the increasing demands for basic human needs and welfare. In Ethiopian condition there is an urgent need to design and implement appropriate land management options, coupled with population control and sustainable natural resource use and conservation that meet the need of both present and future generations [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: Land Use/land Cover Change and Soil Erosion In Ethiopiamentioning
confidence: 99%
“…Support practice factor (P) describes the effectiveness of erosion control measures like contours, strip cropping and terracing to reduce soil loss rate from its average rate from unprotected land to tolerable estimated rate (Esa et al, 2018). The lesser P value represents the more effective support practice to reduce soil erosion and the larger P value represents the lesser effective support practice to reduce soil erosion (Adugna et al, 2015). The P values vary from 0 to 1, where the value 0 represents a very good erosion resistance practice and the value 1 represents no resistance practice.…”
Section: Support Practice Factor (P)mentioning
confidence: 99%